Online gambling: A treatment for sports betting addiction - Marcos, Marta (2020)
Background: online gambling (bets, casino games, poker, etc.) is an activity that is spreading worldwide, even in countries where it is not yet legalized. Although the situation in Latin America is very heterogeneous, it is possible that, as online gambling is developed and promoted, addiction problems arise. This has already happened in Spain since the legalization of online gambling in 2011. Thus, psychology should be developing intervention programs to face this new scenario. Goal: this paper describes the treatment protocol for a young man with sports betting addiction. Method: the treatment proposal consisted in a cognitive behavioral therapy which focused on deconditioning of gambling situations; training of skills needed to prevent relapses and overcome risky situations; information on gambling risks; change of attitude towards gambling; and promotion of a healthy lifestyle incompatible with gambling addiction. Results: both the treatment phases and the theoretical basis of the intervention proposal are described. The patient, diagnosed with a severe gambling disorder, showed improvements in the gambling disorder criteria and the Symptom Severity Scale Score. Conclusions: a treatment protocol for online gambling addiction, which is based on the principles of motivation and learning, has been developed. This protocol has demonstrated to be effective in reducing gambling behavior and promoting a new healthy lifestyle.